Effect of Stretching Force on the Cells of Epithelial Rests of Malassez In Vitro - Teruyoshi Koshihara; Kenichi Matsuzaka; Toru Sato; Takashi Inoue (Hindawi Limited, 2010)
Background and Objective. The aim of this study was to investigate the behavior of cells from epithelial rest of Malassez (ERM) against stretching force. Material and Methods. ERM-cultured cells were stretched for 1 hour, at the cycle of 18% elongation for 1 second followed by 1-second relaxation. The cells without addition of stretching force were used as controls. The cells were observed by immunohistochmical staining using actin 0, 12, 24, 36, 48, and 72 hours. Furthermore, expressions of HSP70-, VEGF-, and OPN-mRNAs of cells were also evaluated using quantitative RT-PCR. Results. Actin filaments were randomly orientated in the cytoplasm in the control group, whereas in the stretching group, actin filaments were orientated comparatively parallel to the stretching direction. Expression of HSP70-mRNA in the stretching group was significantly higher than that of control group at 12, 24, 36 hours (P<.05). Expression of VEGF-mRNA in the stretching group was significantly higher than that of control group at 24, 36, 48, and 72 hours (P<.05). Expression of OPN-mRNA in the stretching group was significantly higher than that of control group at 12 and 24 hours (P<.05). Conclusion. ERM cells response against the stretching force by expressing HSP70, VEGF, and OPN.